(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Osteoarthritis (OA) is one of the most common chronic joint diseases, representing an important medical and social problem due to its progressive course, pain, and reduced quality of life. Osteoarthritis of the knee (gonarthrosis) is the most prevalent form of OA and a frequent cause of loss of work capacity and disability. According to the Global Burden of Disease 2019, around 7% of the world’s population (more than 500 million people) suffers from osteoarthritis [1]. Prevalence increases with population aging and the obesity epidemic: OA accounts for up to 65–70% of all rheumatic diseases in the elderly, and radiological signs are found in 80% of people over 60 years. Meanwhile, incidence before age 50 is low (only 3–5%) but rises sharply in older age groups [2]. In real-world conditions, the figures may be even higher, considering that many patients do not seek help in a timely manner. In Uzbekistan, as in the rest of the world, OA is becoming an increasingly pressing issue. Precise epidemiological data on early knee OA in the region are scarce; however, it is known that musculoskeletal diseases rank third among the overall morbidity of adults [3, 4]. The high prevalence of risk factors – in particular, excess body weight in the population (per WHO, 50% of adults 18–64 in Uzbekistan are overweight and 20% have obesity) – contributes to a significant burden of knee OA in the country. Thus, the problem of early osteoarthritis of the knee joints (early knee OA, EKOA) is extremely urgent, requiring attention to early diagnosis and multidisciplinary patient management.